On the desire to levitate : poems - Powell, Alison, 1979- (Ohio University Press, 2014)
"On the Desire to Levitate is the first collection of poems by Alison Powell. This striking collection includes vivid, unflinching meditations on aging, mythology, poetry, and family. In tight, elegant lines that alternate between homage and elegy, these poems explore known subjects with a rebellious eye: a defeated Hercules and a bitter Eurydice, a sympathetic Lucifer, and generations of adolescent girls as mythical adventurers moving within a beloved but confining Midwest. Yet in Powell's skillful hands, hardship never overtakes: as judge Charles Hood writes, "There's often a delicious humor in this work, and always a deep and lasting integrity.""--